Struktur Modal Dan Likuiditas Terhadap Nilai Perusahaan : Ukuran Perusahaan Sebagai Variabel Moderasi - Sri Ayem; Chanderika Rambu Tamu Ina (Yayasan Literasi Ilmiah Indonesia, 2023)
Purpose: This study aims to obtain empirical evidence of the effect of capital structure and liquidity on firm value with firm size as a moderated variable. Method: Sampling used purposive sampling method and produced 45 samples data. Data analysis techniques with multiple linear analysis and Moderated Regression Analysis (MRA) Finding: The results obtained indicate that the capital structure has no effect on firm value. Liquidity has a negative effect on firm value. Firm size can moderate the positive effect of capital structure on firm value, and firm size can moderate negative effect of liquidity on firm value. Novelty: This study considers the effectiveness of the involvement of firm size as a moderating factor of the influence of capital structur and liquidity on firm value ini food and beverage companies. Keywords: Capital structure, Liquidity, Firm Value, Firm size